2016
DOI: 10.1177/1558689816633310
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Mixed Methods Instrument Development and Construct Validation Process: The Transformative Experience Questionnaire

Abstract: Onwuegbuzie and colleagues proposed the Instrument Development and Construct Validation (IDCV) process as a mixed methods framework for creating and validating measures. Examples applying IDCV are lacking. We provide an illustrative case integrating the Rasch model and cognitive interviews applied to the development of the Transformative Experience Questionnaire (TEQ). TEQ measures student engagement with the content they are learning. IDCV process yielded a high degree of utility for informing the psychometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
0
30
0
1
Order By: Relevance
“…TE was measured using a 27‐item Likert scale modified from an instrument, the Transformative Experience Scale (TES), designed, and validated in previous research by Pugh and colleagues (Koskey, Sondergeld, Stewart, & Pugh, ; Pugh et al., ). The survey was delivered pre‐ and post‐intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TE was measured using a 27‐item Likert scale modified from an instrument, the Transformative Experience Scale (TES), designed, and validated in previous research by Pugh and colleagues (Koskey, Sondergeld, Stewart, & Pugh, ; Pugh et al., ). The survey was delivered pre‐ and post‐intervention.…”
Section: Methodsmentioning
confidence: 99%
“…TES had a high reliability score (pretest: α = .97; posttest: α = .98). TES was designed based on the TE theoretical framework and includes all three components of TE and content validity as evidenced by Koskey and colleagues () who performed a factor analyses and showed that the instrument has three distinct dimensions in alignment with theory. We modified the instrument to fit our content area and did not change the wording otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…E.g., we added a four-point Likert scale question on confidence in institutional computer security measures (with an open-ended follow-up question), and a yes/no/not sure question on perceived behavior change (also with an open-ended follow-up). To further validate the refined survey instrument [13], the instrument was reviewed by two survey experts and two additional domain experts. We also performed two formal cognitive walkthroughs with pseudo-participants (persons representative of the participant sample, but who were not part of the sample).…”
Section: Instrument Developmentmentioning
confidence: 99%
“…This framework guided the development of an evaluative tool from the mixed‐methods data combined from contextualized components of the Intervention Wheel framework and conceptual model for social programmes. Koskey, Sondergeld, Stewart, and Pugh () also used the IDCV mixed‐methods framework in the development of a questionnaire on a transformative experience. As a method, this framework shows promise in the development of much‐needed tools to evaluate public health care services.…”
Section: Discussionmentioning
confidence: 99%